Reducing False Positives in a Computer-Aided Diagnosis Scheme for Detecting Breast Microcalcificacions: A Quantitative Study with Generalized Additive Models - Roca-Pardinas, Istvan FeherJavier; Lado, Maria J.; Tahoces, Pablo G.; Suarez, Carmen Cadarso (IntechOpen, 2012)
None